Enhanced “In Vitro“ Release of Platelet α-Granules After Acute Myocardial Infarction (AMI) - Pengo, V; Boschello, M; Prandoni, P; Schiavon, R; Bellotto, F; Schivazappa, L; Dalla Volta, S (Thrombosis and Haemostasis, 1985)
In vivo platelet activity was studied in 58 patients with AMI on admittance to the Coronary Care Unit, in 48 of these patients after 1 week, in 30 after 1 month and in 24 patients after 6 months. Patients were carefully selected and excluded if they had associated diseases known to increase platelet activity. In vivo activation was studied by evaluating the plasma concentration of beta-thromboglobulin (β-TG) and platelet factor 4 (PF4) in the same blood sample. On admittance (x = 58.5) and on day 7 (x = 52.9) β-TG values were significantly higher than those obtained in the control group (x = 29). β-TG values were moderately elevated after 1 month (x = 37.7) and then returned to values similar to those of the control group after 6 months (x = 27.9). The simultaneous assessment of PF4 shows a β-TG/PF4 ratio indicative for in vitro release (≤2.5) in many patients on days 1 and 7. Moreover, the β-TG/PF4 ratio in patients with AMI tends towards 2 when β-TG values are high. These results may indicate a greater tendency to an in vitro platelet release in the acute phase of AMI.
Keywords: β-TG; PF4; AMI